Spain´s Foreign Policy towards the Asia-Pacific: From non-Existent to Insufficient - Abad, Gracia (UNISCI Discussion Papers, 2011)
This article analyses the efforts made by Spain over the last decade in order to strengthen its role in a geographical area from which it has been largely absent: Asia. Such efforts, motivated to a great extent by the growing weight of Asia in the international context have found a powerful instrument in the Asia-Pacific Plans; likewise they have resulted in a greater Spanish presence in the region as well as in an increase in the exchanges with it. However, a long way lies still ahead and the initiatives undertaken so far will need to be continued and deepened.
Keywords: Spain; Pacific-Asia; Foreign Policy; Asia-Pacific Plan.